2020
DOI: 10.34117/bjdv6n11-576
|View full text |Cite
|
Sign up to set email alerts
|

Gestão De Resíduos De Construção E Demolição No Município De Belo Horizonte: Uma Abordagem Para a Sustentabilidade / Construction and Demolition Waste Management in the City of Belo Horizonte: An Approach to Sustainability

Abstract: Gestão de resíduos de construção e demolição no Município de Belo Horizonte: uma abordagem para a sustentabilidade Construction and demolition waste management in the City of Belo Horizonte: an approach to sustainability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In particular, ACBM wastes that are highly deteriorated, broken, or fragmented can release fibers only with hand pressure and represent a higher risk for the population and the environment (Paglietti et al, 2016). Thus, ACBM waste exhibits hazardous characteristics that require special management and strict controls (Szymańska & Lewandowska, 2019), which also precludes ACBM waste recycling and requires an appropriate final disposal (del Río Merino et al, 2010; Li et al, 2014; Quaranta et al, 2010; Raleigh et al, 1995; Silva Santos & Penteado Marchesini, 2018). Related to ACBM waste recycling, during this research, a store that purchases and sells recycled ACBM waste was identified near the city of Bogotá, the capital of Colombia (see Supporting Information: Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ACBM wastes that are highly deteriorated, broken, or fragmented can release fibers only with hand pressure and represent a higher risk for the population and the environment (Paglietti et al, 2016). Thus, ACBM waste exhibits hazardous characteristics that require special management and strict controls (Szymańska & Lewandowska, 2019), which also precludes ACBM waste recycling and requires an appropriate final disposal (del Río Merino et al, 2010; Li et al, 2014; Quaranta et al, 2010; Raleigh et al, 1995; Silva Santos & Penteado Marchesini, 2018). Related to ACBM waste recycling, during this research, a store that purchases and sells recycled ACBM waste was identified near the city of Bogotá, the capital of Colombia (see Supporting Information: Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The final disposal of ACBM waste must be carried out under controlled conditions to prevent or minimize the release of asbestos fibers. For this reason, in addition to international regulations (Australian New South Wales Governor, 2014; Italian Ministry of Environment and Land Protection, 2004; UK Health and Safety Executive, 2012; US Environmental Protection Agency, 2011), the scientific literature agrees that the recommended technique for final disposal is a licensed ACBM waste landfill cell specially designed for this purpose (del Río Merino et al, 2010; Gualtieri, 2012; Klojzy‐Karczmarczyk & Staszczak, 2018; Paglietti et al, 2012; Powell et al, 2015; Silva Santos & Penteado Marchesini, 2018; Wallis et al, 2020). Therefore, ACBM waste should not be disposed of in CDW final disposal sites or informal CDW dumps.…”
Section: Resultsmentioning
confidence: 99%
“…The uniqueness of the artisanal açaí whisk is highlighted by Silva, when he says that the existence of "acai spots" is a unique invention of the population of Belém, which completely depends on the local habit of consuming the pulp of the fruit as a basic meal, Furthermore, the numerical significance of these micro-entrepreneurs instigates studies, so that the phenomenon is highlighted by Costa (2017), when he expresses that only in the city of Belém, capital of the State of Pará, there are more than 3 thousand scouts [1]. Araújo (2017) complements by expressing that from an economic point of view, the açaí fruit is representative in the local, national and international scenario.…”
Section: Introductionmentioning
confidence: 99%